ANALISIS METODE TAFSIR WAHBAH ZUHAILI DALAM KITAB AL-MUNIR - Andy Hariyono (STIQ al-Lathifiyyah Palembang, 2018)
This paper discusses the Wahbah Zuhaili tafsir method used in writing the Al-Munir tafsir. When the Messenger of Allah (peace be upon him) was still in the midst of the ummah, all the problems including the tafsir of the Quran were returned to him. At least the interpretation model that developed at that time was the Prophet (PBUH) to answer the questions of the Companions— Radhiyallahu'anhum—or his companions. reading and listening to the Koran then they understand the laws that are certainly confirmed by the Prophet. This kind of interpretation model at that time has not yet been written. because there is a ban from the Messenger of Allah, it is feared that there is a mix between the Quran and so on. But in certain cables the Prophet allowed some friends to write it down. This study attempts to understand the concept of the scholar's tafsir of Wahbah Zuahaili in his interpretation of 'Tafsir Al-Munīr fi'l Aqida wa's Shari'ah wa'l Manhaj by using a literature study approach, this study besides revealing the interpretation method, also describing the findings and contributions of the one of the references in the science of tafsir.